2020
DOI: 10.3390/agriculture10100488
|View full text |Cite
|
Sign up to set email alerts
|

The Thin Line between Pathogenicity and Endophytism: The Case of Lasiodiplodia theobromae

Abstract: Many fungi reported for endophytic occurrence are better known as plant pathogens on different crops, raising questions about their actual relationships with the hosts and other plants in the biocoenosis and about the factors underlying the lifestyle shift. This paper offers an overview of the endophytic occurrence of Lasiodiplodia theobromae (Dothideomycetes, Botryosphaeriaceae), a species known to be able to colonize many plants as both an endophyte and a pathogen. Prevalently spread in tropical and subtropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 125 publications
0
31
0
1
Order By: Relevance
“…As known for many other plant pathogens, these fungi may present a latent stage during the disease cycle which can imply their possible recovery from asymptomatic tissues. In fact, recent investigations on microbial symbionts of several plant species are disclosing cases where fungal pathogens may persist in the endophytic condition for prolonged periods [ 70 , 71 , 72 ], supporting the hypothesis that at least some strains could behave as true endophytes in the absence of factors stimulating their pathogenicity. In the case of C. sativa , this aspect has been proposed as a possible explanation for the recovery of C. parasitica from asymptomatic coppice shoots of C. sativa in Switzerland [ 28 ].…”
Section: Occurrence Of Endophytic Fungi In Chestnuts and Ecologicamentioning
confidence: 93%
“…As known for many other plant pathogens, these fungi may present a latent stage during the disease cycle which can imply their possible recovery from asymptomatic tissues. In fact, recent investigations on microbial symbionts of several plant species are disclosing cases where fungal pathogens may persist in the endophytic condition for prolonged periods [ 70 , 71 , 72 ], supporting the hypothesis that at least some strains could behave as true endophytes in the absence of factors stimulating their pathogenicity. In the case of C. sativa , this aspect has been proposed as a possible explanation for the recovery of C. parasitica from asymptomatic coppice shoots of C. sativa in Switzerland [ 28 ].…”
Section: Occurrence Of Endophytic Fungi In Chestnuts and Ecologicamentioning
confidence: 93%
“…The most commonly found genera, Lasiodiplodia , Fusarium , and Aspergillus , are all ubiquitous in both endophytic and other contexts. The genus Lasiodiplodia is best known for the species Lasiodiplodia theobromae , a prevalent endophyte in the global tropics ( Salvatore and Andolfi, 2020 ), but also an infamous pathogen of tropical fruit trees. For instance, L. theobromae has been found to cause crown rot in commercial banana ( Sangeetha et al, 2012 ) and–among other Lasiodiplodia strains–stem and fruit rot in papaya ( Netto et al, 2014 ) and dieback in mango ( Rodríguez-Gálvez et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Symbiotic association between a fungus and a plant is a widespread phenomenon in nature and several symbiotic lifestyles have been defined considering the benefits to or impacts on host and symbiont [7]. Recent studies have indicated that botryosphaeriaceous fungi may express different symbiotic lifestyles in response to host internal signals or environmental factors which also influence the secondary metabolites production [8][9][10][11][12]. In fact, secondary metabolites may have a crucial role in the fungal lifestyles because these compounds have a broad number of biological functions, including mediating communication, nutrient acquisition and acting as virulence factors [13,14].…”
Section: Secondary Metabolitesmentioning
confidence: 99%
“…One of the major concerns in GTDs control is the slow progression of the host xylem colonization by pathogenic fungi or the absence of symptoms for long periods [71,73,74]. In the broad spectrum of GTDs, species of Botryosphaeriaceae are the disease causative agent of the Botryosphaeria dieback [12,58,75] and several of these species belong to genus Neofusicoccum, causing diverse symptoms in infected grapevines, such as leaf chlorosis, bud and wood necrosis, weak spring growth, and vascular cankers primarily in the shape of wedges [72,76,77]. Many symptoms, particularly the foliar ones, can be attributed to the production of toxic secondary metabolites by the fungus [11,78].…”
Section: Phytotoxicity Of Neofusicoccum Metabolites On Grapevinementioning
confidence: 99%